1965
DOI: 10.1111/j.1151-2916.1965.tb14648.x
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Plastic Deformation of Polycrystalline Beryllium Oxide

Abstract: High‐density specimens were plastically deformed under four‐point transverse bending. Tests were conducted in vacuum in the region 1400° to 1700°C under stresses of 1000 to 4500 psi. The activation energy for creep was 99.0 kcal/mole. Creep rate was directly proportional to the applied stress and inversely proportional to the square of the grain diameter. The deformation behavior is ascribed to a Nabarro‐Herring type mechanism. Results show that creep was the same in tension and compression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1971
1971
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Activation Energy Q The activation energy is large (100 kcal mole-a), but similar values have been observed in creep [5] and sintering [13] experiments in BeO. Most published values of activation energies for cation and anion self-diffusion in BeO fall in the range 50 to 60 kcal mole -1 [14][15][16] however, there is evidence to suggest that these values are associated with impurity effects.…”
Section: Mean Values Of the Apparent Activation Volumesupporting
confidence: 57%
See 2 more Smart Citations
“…Activation Energy Q The activation energy is large (100 kcal mole-a), but similar values have been observed in creep [5] and sintering [13] experiments in BeO. Most published values of activation energies for cation and anion self-diffusion in BeO fall in the range 50 to 60 kcal mole -1 [14][15][16] however, there is evidence to suggest that these values are associated with impurity effects.…”
Section: Mean Values Of the Apparent Activation Volumesupporting
confidence: 57%
“…Fig. 3 shows a 284 The present data cannot be interpreted in terms of a creep law with the first power of the stress (/3 = 1 over the stress range in the beam) such as has been suggested from higher temperature creep data [5].…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Additionally, dislocations were shown to contribute to deformation of polycrystalline ceramics at high temperatures (e.g., >1000 • C). [10][11][12][13][14][79][80][81] Furthermore, it was demonstrated that dislocations could even increase the toughness of ceramics. 36,82,83…”
Section: Fundamental Aspects Of Dislocations In Ceramicsmentioning
confidence: 99%
“…In consequence, ideas can remain within their fields while there are few overarching reviews so far. For example, knowledge on room temperature plasticity of a whole range of ceramic single crystals [6][7][8][9] or plasticity of polycrystals at elevated temperature [10][11][12][13][14][15] is currently not wide spread.…”
Section: Introductionmentioning
confidence: 99%